Exogenous Factors from Animal Sources that Induce Platelet Aggregation - Chow, Geraldine; Kini, R. Manjunatha (Thrombosis and Haemostasis, 2001)
Platelets clump together by two different processes: agglutination and aggregation. Agglutination is a passive process, independent of the metabolic status of the platelets. It is a physical phenomenon of binding of a protein or glycoprotein, which has two or more binding domains. In contrast, platelet aggregation is a metabolically active, transmembrane process that requires “live” platelets. It involves activation, shape change, secretion and adhesion. Following the change in light transmission in turbidometric aggregometers, one can monitor both the processes. Only agglutination can be induced in formaldehyde-fixed platelets, but not aggregation. PGE1 inhibits aggregation, but not agglutination. Metabolic inhibitors, such as antimycin A and 2-deoxy-D-glucose, are also used to distinguish aggregation and agglutination. Some exogenous factors isolated from animal sources induce platelet agglutination, whereas others induce aggregation. In this inventory, when possible, we will distinguish between these effects. Some of these factors exhibit phospholipase A2 (PLA2) and proteinase activities, whereas others lack enzymatic activity. Aggregation inducers are divided into three main groups: factors that directly act on platelets (Group I); factors that require a plasma component (Group II); and heterogeneous and partially characterized factors with unknown mechanisms (Group III).